Preparation method for realizing controllable specification of cellulose nanocrystals by virtue of maleic acid hydrolysis under synergistic assistance of ferric chloride catalysis and microjet machinery

Through the coordinated auxiliary maleic acid hydrolysis method of iron chloride catalysis and microjet mechanical, the problems of high cost, unenvironmental processes and difficult to regulate the characteristics of nanocellulose preparation are solved, and efficient and environmentally friendly nanocellulose preparation is achieved, improving the improvement of nanocellulose preparation Its thermal stability and application potential are achieved.

CN119219797APending Publication Date: 2024-12-31SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411264830.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the industrial production of nanocellulose has problems such as high preparation costs, unenvironmental processes, poor thermal stability, low crystallinity and difficult to regulate characteristics and specifications, which are difficult to meet the requirements of green environmental protection and high efficiency.

Method used

Using iron chloride catalysis and microjet mechanical auxiliary maleic acid hydrolysis method, the specifications of cellulose nanocrystals can be controlled through maleic acid hydrolysis reaction, suction filtration washing, dialysis treatment and microjet homogenization treatment, which improves the specifications of cellulose nanocrystals. The yield and characteristics of CNC reduce energy consumption and waste liquid emissions.

Benefits of technology

It realizes efficient and environmentally friendly nanocellulose preparation, improves the yield and characteristic specifications of CNC, reduces production costs and energy consumption, and enhances its application potential in reinforced materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219797A_ABST
    Figure CN119219797A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for realizing controllable specification of cellulose nanocrystals by virtue of maleic acid hydrolysis synergistically assisted by ferric chloride catalysis and microjet machinery. The method comprises the following steps: (1) preparing a maleic acid solution, proportioning a ferric chloride solution, mixing and heating, and then adding a cellulose raw material for hydrolysis; (2) carrying out vacuum filtration and washing a fiber suspension obtained by acidolysis; (3) diluting the fiber filter residue, and pressurizing and homogenizing through a nano micro-jet homogenizer; and (4) carrying out centrifugal operation, collecting supernate to obtain CNC turbid liquid, and drying to obtain CNC. Agents used in the invention are green and environment-friendly and can be recycled, the reaction conditions are relatively mild, the process is easy to control, the operation process is simple, and the prepared product has excellent performances such as controllable specification, good dispersion stability and good thermal stability. The CNC prepared by the method has wide application prospects in biomedicine, food packaging, beauty makeup skin care products and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of natural polymer material preparation, and specifically relates to a preparation method for cellulose nanocrystals with controllable specifications by using ferric chloride catalysis and microfluidics mechanical synergistic assistance of maleic acid hydrolysis. Background Art

[0002] Due to the demand for sustainable development, in order to ease the pressure on resources and energy brought by industrial development, more and more researchers have turned their attention to the natural nano-polymer material nanocellulose, which has a wide source, abundant output and is degradable. Nanocellulose is prepared by nano-nano-cellulose, including cellulose nanocrystals (CNC) and cellulose nanofibrils (CNF), where CNC refers to rod-shaped fiber crystals with a width and length of 5~70nm and several hundred nanometers respectively; CNF refers to entangled nanofibers with a diameter of 5~60nm and a length of several microns. CNC has the advantages of high aspect ratio, large specific surface area, excellent mechanical modulus and easy surface chemical modification, and has been widely used as a filler to enhance nanocomposites. Due to its safety and effectiveness, it has shown great potential in many fields such as biomedical materials, packaging materials, and electrode materials.

[0003] However, the industrial production of CNC has not yet been perfected. The high preparation cost and environmentally unfriendly process have become major bottlenecks restricting the development of related nanomaterials. The most traditional CNC prepared by the hydrolysis method of inorganic strong acid (sulfuric acid, phosphoric acid, hydrochloric acid, etc.) has poor thermal stability, low crystallinity, small aspect ratio, and will cause serious environmental problems such as equipment corrosion and waste liquid pollution. The mild bio-enzyme hydrolysis method is costly, time-consuming, low yield, and messy specifications, making it difficult to achieve industrial production. In addition, due to the natural reaction behavior characteristics of various reagents, the above preparation methods also generally have the problem that the important characteristics and specifications of CNC are difficult to adjust on demand, such as crystallinity, aspect ratio, surface carboxyl content, etc., which are crucial for the subsequent application of CNC. At this stage, companies with large-scale preparation of nanocellulose are basically still using methods such as inorganic strong acid hydrolysis and TEMPO (2,2,6,6-tetramethylpiperidin-N-oxyl free radical) oxidation, which are highly polluting and energy-intensive, and it is difficult to meet the national "dual carbon" goals. Therefore, developing green, environmentally friendly, efficient and highly tunable preparation technologies will be the main direction for the future development of nanocellulose.

[0004] Related studies have shown that green and recyclable organic acids (such as formic acid, butyric acid, p-toluenesulfonic acid, citric acid, etc.) can be used to hydrolyze cellulose raw materials to prepare CNC. Compared with traditional methods, organic acid hydrolysis has the advantages of mild reaction conditions, low corrosion to equipment, high acid recovery rate and environmental friendliness. Some polybasic organic acids (such as oxalic acid, maleic acid, citric acid, etc.) contain more than two carboxylic acid functional groups and have multiple ways to react with cellulose. The prepared CNC has a certain amount of carboxyl groups and has greater functional application potential. However, due to the weak acidity of organic acids, there are problems such as long reaction time of single organic acid hydrolysis and low CNC yield. The yield can be improved by adding inorganic strong acid catalysts (such as sulfuric acid and hydrochloric acid), but these catalysts are toxic and non-recyclable, which greatly limits the application of CNC in food, medicine, cosmetics and skin care products, and cannot meet the requirements of green preparation and high value-added application at the same time.

[0005] Maleic acid has moderate acidity among common organic carboxylic acids. Scientific physical assisted hydrolysis of maleic acid is an effective means to increase the yield of CNC. Microfluidizer has the advantages of short-term high efficiency, convenient operation, and can be applied to large-scale industrial production. Through homogenization, CNC can be separated from the fiber to a greater extent, and the hydrogen bond force between the fiber fibrils can be effectively weakened through physical action, so that the size of all fiber slurries can be uniformly reduced, further improving the yield of CNC and effectively reducing the diameter of CNC products. In addition, maleic acid can be converted into cyclic anhydride under certain heating conditions, and cyclic anhydride can more effectively react with the hydroxyl groups on the surface of cellulose to undergo acylation, thereby giving the CNC product surface more carboxyl groups, which not only increases the subsequent functionalization pathways of CNC, but also effectively increases the surface charge density of CNC, and can be better dispersed in aqueous solvents.

[0006] In addition, ferric chloride is a solid inorganic salt that is harmless to the environment. It has good selectivity and catalytic activity for the hydrolysis of natural polysaccharides. It can effectively improve the efficiency of cellulose hydrolysis in the preparation of CNC, while reducing energy consumption in production. More importantly, due to the selectivity of ferric chloride for the hydrolysis of polysaccharide glycosidic bonds, the length of CNC products can be effectively regulated by regulating it, and accordingly, the carboxyl content on the surface of CNC can also be affected to a certain extent. After the hydrolysis, the mixture of ferric chloride and maleic acid can also be recovered and reused by acid-base neutralization reaction, crystallization and other methods. This process is green, environmentally friendly, efficient and economical, produces fewer side reactions, and has a low risk of corrosion to instruments. Therefore, the combination of the three will greatly improve the yield of CNC while effectively regulating its aspect ratio, carboxyl content and even cleanliness and other characteristic specifications, and the overall process has low waste liquid and waste emissions, low energy consumption and low cost.

[0007] At present, there is no report on the preparation method of CNC with controllable specifications by ferric chloride catalysis and microfluidics synergistic hydrolysis of maleic acid. Summary of the invention

[0008] In view of the low yield of nanocellulose prepared by organic acid method and the uncontrollable characteristic specifications, the present invention proposes a method for preparing cellulose nanocrystals (CNC) by ferric chloride catalysis and microfluidic mechanical assisted maleic acid hydrolysis, and at the same time, the CNC specifications can be controlled. In addition to obtaining the upper light blue CNC suspension, the lower precipitate can also be collected to obtain a colloidal cellulose nanofibril (CNF) suspension, with a total recovery rate of 95%; the used drugs can be recycled and reused. The overall process is simple, efficient, economical and environmentally friendly.

[0009] The purpose of the present invention is to provide a method for preparing CNC with controllable specifications by promoting the hydrolysis of maleic acid by utilizing the synergistic effect of ferric chloride catalysis and microfluidic mechanical assistance. The process is green and environmentally friendly, and the materials used are non-toxic and harmless. The prepared CNC has a high carboxyl content, which is conducive to later functionalization. At the same time, the CNC has the advantages of high surface electronegativity and high thermal stability, and has application potential in the fields of biomedicine, tissue engineering, food health care, and beauty and daily chemicals.

[0010] The purpose of the present invention is achieved by at least one of the following technical solutions.

[0011] A method for preparing cellulose nanocrystals with controllable specifications by hydrolyzing cellulose with maleic acid catalyzed by ferric chloride and assisted by microfluidics, comprising the following steps: S1. Maleic acid hydrolysis reaction Prepare maleic acid aqueous solution, mix with ferric chloride solution, heat, add fiber raw material to carry out hydrolysis reaction; S2. Filtration, washing and maleic acid recovery The hydrolyzed fiber suspension is vacuum filtered and washed to obtain a filtrate and a filter residue, and a mixture of maleic acid and ferric chloride in the filtrate is recovered; S3. Dialysis treatment Dialyze the filter residue in S2 with deionized water to obtain the retained solution; S4. Microfluidizer Homogenizer The dialyzed retained solution is diluted with deionized water (preferably diluted to a mass concentration of 0.5 wt%), and pressure homogenized by a microfluidizer to obtain a colloidal nanocellulose mixed solution; S5. Centrifuge the nanocellulose mixture, the supernatant is CNC dispersed in water, which is light blue and transparent; collect the turbid liquid to obtain CNF suspension, and dry to obtain solid CNC or CNF.

[0012] The following is a preferred technical solution of the present invention: Preferably, in step S1, the mass concentration of the maleic acid aqueous solution is 50-80%, the mass ratio of the fiber raw material to the maleic acid solution is 1:20, and the reaction temperature is 80-100°C.

[0013] Preferably, in step S1, the mass ratio of ferric chloride in the ferric chloride solution to maleic acid is 0.259-2.333.

[0014] Preferably, in step S1, the speed of the mechanical stirring is 300-500 r / min, and the hydrolysis reaction time is 0.5-6 hours.

[0015] Preferably, in step S2, the vacuum filtration is performed using a G4 sand core funnel, and deionized water is continuously added for filtration and washing, and the mass ratio of deionized water to maleic acid solution is 8-6.

[0016] Preferably, in step S2, the method for recovering maleic acid in the filtrate comprises rotary evaporation, cooling crystallization and reduced pressure distillation.

[0017] Preferably, in step S3, the dialysis treatment is to dialyze the filter residue with deionized water until the conductivity is the same as that of the deionized water; and the retained liquid is the material in the dialysis bag that has not been dialyzed out of the bag.

[0018] Preferably, in step S4, the microfluidizer uses a D8 (200 nm) high-pressure reaction chamber, the homogenization pressure is 9000 psi-16000 psi, and the homogenization times are 1 to 7 times.

[0019] Preferably, in step S5, the centrifugal condition is 8000-10000 r / min, centrifugation is performed for 15 min and the supernatant is collected.

[0020] Preferably, in step S5, the drying is freeze-drying or spray-drying.

[0021] The present invention also provides a CNC prepared by the above preparation method.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The preparation of CNC by hydrolyzing cellulose raw materials with maleic acid has the characteristics of wide raw material sources, low risk and cost in the preparation process, and environmental protection and no pollution. It meets the requirements of coexistence of sustainable production and environmental protection. Compared with the traditional inorganic acid hydrolysis method for preparing CNC, it uses less water, has a clean and environmentally friendly process, and has no equipment corrosion. Compared with other methods for preparing CNC by maleic acid hydrolysis, the CNC yield of this method is significantly improved, the catalyst is safe, harmless, green and safe, and the introduction of harmful substances and the cost of catalyst recovery are reduced.

[0023] (2) The ferric chloride solution used in the present invention catalyzes the hydrolysis of maleic acid, effectively improving the hydrolysis efficiency, and can adjust the CNC aspect ratio and carboxyl content and other characteristic specifications as needed, and significantly reduce the energy consumption in production, which is conducive to the large-scale industrial production of CNC.

[0024] (3) The nano-micro jet homogenization auxiliary means adopted in the present invention has high efficiency, short aging time, simple feeding and discharging methods, and is suitable for industrial production.

[0025] (4) Through homogenization treatment, CNC can be separated from the fiber and the size of the fiber slurry can be uniformly reduced, thereby increasing the yield of CNC and residual CNF to a greater extent.

[0026] (5) The maleic acid used in the present invention can be successfully recovered and recycled, with a recovery rate of more than 85%, and the CNC yield after reuse decreases slightly.

[0027] (6) The present invention prepares CNC with high yield and controllable specifications through a simple one-step method. The obtained CNC has good dispersion stability and thermal stability. The above excellent properties increase its application potential in various types of reinforcement materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a photograph of a suspension of CNC prepared by maleic acid hydrolysis dispersed in water.

[0029] Figure 2 It is an atomic force electron microscopy image of CNC prepared by maleic acid hydrolysis.

[0030] Figure 3 It is the size and aspect ratio of the prepared CNC. DETAILED DESCRIPTION

[0031] The content of the present invention is further illustrated below in conjunction with specific examples, but it should not be understood as limiting the present invention. Without departing from the spirit and essence of the present invention, simple modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention; unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0032] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.

[0033] Example 1: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 0.259 g of ferric chloride, and react at 100°C and 300 r / min for 0.5 h to obtain a hydrolyzed suspension.

[0034] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0035] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized three times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0036] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0037] (5) The yield of the obtained CNC was 46.2%, the aspect ratio was 50.3, the carboxyl content was 0.61 mmol / g, and the crystallinity was 72.3%.

[0038] Example 2: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 0.5 h to obtain a hydrolyzed suspension.

[0039] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0040] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized three times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0041] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0042] (5) The yield of the obtained CNC was 62.8%, the aspect ratio was 35.2, the carboxyl content was 0.78 mmol / g, and the crystallinity was 74.1%.

[0043] Example 3: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 2.333 g of ferric chloride, and react at 100°C and 300 r / min for 0.5 h to obtain a hydrolyzed suspension.

[0044] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0045] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized three times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0046] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0047] (5) The yield of the obtained CNC was 50.2%, the aspect ratio was 21.8, the carboxyl content was 0.92 mmol / g, and the crystallinity was 71.8%.

[0048] Example 4: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 50%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 0.5 h to obtain a hydrolyzed suspension.

[0049] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0050] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized three times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0051] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0052] (5) The yield of the obtained CNC was 50.3%, the aspect ratio was 48.1, the carboxyl content was 0.43 mmol / g, and the crystallinity was 69.8%.

[0053] Example 5: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 65%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 0.5 h to obtain a hydrolyzed suspension.

[0054] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0055] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized three times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0056] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0057] (5) The yield of the obtained CNC was 53.7%, the aspect ratio was 39.7, the carboxyl content was 0.59 mmol / g, and the crystallinity was 71.3%.

[0058] Example 6: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 0.5 h to obtain a hydrolyzed suspension.

[0059] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0060] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized five times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0061] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0062] (5) The yield of the obtained CNC was 71.2%, the aspect ratio was 41.5, the carboxyl content was 0.78 mmol / g, and the crystallinity was 72.6%.

[0063] Example 7: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 0.5 h to obtain a hydrolyzed suspension.

[0064] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0065] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0066] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0067] (5) The yield of the obtained CNC was 79.4%, the aspect ratio was 56.2, the carboxyl content was 0.78 mmol / g, and the crystallinity was 70.8%.

[0068] Example 8: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0069] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0070] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0071] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0072] (5) The yield of the obtained CNC was 82.3%, the aspect ratio was 49.2, the carboxyl content was 0.81 mmol / g, and the crystallinity was 72.1%.

[0073] Example 9: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 6 h to obtain a hydrolyzed suspension.

[0074] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0075] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0076] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which was light blue and transparent. CNC was obtained by freeze drying, such as Figure 1 .

[0077] (5) Figure 3 The yield of the obtained CNC was 88.6%, the aspect ratio was 39.6, the carboxyl content was 0.85 mmol / g, and the crystallinity was 74.5%.

[0078] Example 10: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 80°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0079] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0080] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0081] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0082] (5) The yield of the obtained CNC was 78.6%, the aspect ratio was 55.1, the carboxyl content was 0.67 mmol / g, and the crystallinity was 70.3%.

[0083] Example 11: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 90°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0084] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0085] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0086] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0087] (5) The yield of the obtained CNC was 80.5%, the aspect ratio was 52.6, the carboxyl content was 0.73 mmol / g, and the crystallinity was 71.5%.

[0088] Example 12: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 400 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0089] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0090] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0091] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0092] (5) The yield of the obtained CNC was 83.1%, the aspect ratio was 48.5, the carboxyl content was 0.8 mmol / g, and the crystallinity was 71.9%.

[0093] Example 13: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 500 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0094] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0095] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0096] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0097] (5) The yield of the obtained CNC was 83.8%, the aspect ratio was 47.3, the carboxyl content was 0.8 mmol / g, and the crystallinity was 71.3%.

[0098] Example 14: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0099] (2) Add 1400g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0100] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0101] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0102] (5) The yield of the obtained CNC was 83.2%, the aspect ratio was 49.7, the carboxyl content was 0.83 mmol / g, and the crystallinity was 72.9%.

[0103] Example 15: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0104] (2) Add 1200g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0105] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0106] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0107] (5) The yield of the obtained CNC was 82.6%, the aspect ratio was 50.2, the carboxyl content was 0.85 mmol / g, and the crystallinity was 73.2%.

[0108] Example 16: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0109] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0110] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 9000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0111] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0112] (5) The yield of the obtained CNC was 81.2%, the aspect ratio was 55.7, the carboxyl content was 0.72 mmol / g, and the crystallinity was 74.1%.

[0113] Example 17: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0114] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0115] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 12,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0116] (4) The mixed solution was centrifuged at 9000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0117] (5) The yield of the obtained CNC was 80.3%, the aspect ratio was 52.4, the carboxyl content was 0.76 mmol / g, and the crystallinity was 72.9%.

[0118] Example 18: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0119] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0120] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0121] (4) The mixed solution was centrifuged at 8000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which was light blue and transparent. CNC was obtained by freeze drying.

[0122] (5) The yield of the obtained CNC was 81.3%, the aspect ratio was 49.1, the carboxyl content was 0.81 mmol / g, and the crystallinity was 72.1%.

[0123] Example 19: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0124] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0125] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0126] (4) The mixed solution was centrifuged at 10,000 r / min for 15 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0127] (5) The yield of the obtained CNC was 83.4%, the aspect ratio was 49.1, the carboxyl content was 0.81 mmol / g, and the crystallinity was 72.1%.

[0128] Example 20: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidics mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0129] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0130] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0131] (4) The mixed solution was centrifuged at 9000 r / min for 17.5 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which were light blue and transparent. CNC was obtained by freeze drying.

[0132] (5) The yield of the obtained CNC was 82.8%, the aspect ratio was 49.1, the carboxyl content was 0.81 mmol / g, and the crystallinity was 72.1%.

[0133] Example 21: Method for preparing high-yield cellulose nanocrystals (CNC) by maleic acid hydrolysis combined with ferric chloride catalysis and microfluidic mechanical synergistic cleaning (1) Add 10 g of absolutely dry bleached bagasse cellulose to 200 g of maleic acid aqueous solution (mass percentage concentration of maleic acid is 80%), add 10 mL of ferric chloride solution containing 1.296 g of ferric chloride, and react at 100°C and 300 r / min for 3.25 h to obtain a hydrolyzed suspension.

[0134] (2) Add 1600g of deionized water to terminate the reaction and filter the washed suspension. The hydrolyzed suspension is vacuum filtered through a G4 sand core funnel to obtain white solid fibers and filtrate. The solid fibers are poured into a dialysis bag with a molecular weight cutoff of 14,000, and the solid fibers are dialyzed with deionized water until the conductivity is the same as that of deionized water. The filtrate is rotary evaporated at 55-60°C and 150r / min to recover white maleic acid solid, with a recovery rate of more than 85%.

[0135] (3) After dialysis is completed, the retained fibers in the dialysis bag are poured out, diluted with deionized water to form a 0.5 wt% solution, and homogenized seven times by a nano-microfluidizer at a chamber pressure of 16,000 psi to obtain a mixed solution of cellulose nanocrystals and cellulose nanofibrils.

[0136] (4) The mixed solution was centrifuged at 9000 r / min for 20 min until the mixed solution was completely separated to obtain a supernatant and a fiber precipitate. The supernatant was nanocellulose crystals dispersed in water, which was light blue and transparent. CNC was obtained by freeze drying.

[0137] (5) The yield of the obtained CNC was 83.5%, the aspect ratio was 49.1, the carboxyl content was 0.81 mmol / g, and the crystallinity was 72.1%.

[0138] The ferric chloride solution used in the present invention catalyzes the hydrolysis of maleic acid, effectively improves the hydrolysis efficiency, can regulate the characteristic specifications such as CNC aspect ratio and carboxyl content as needed, and significantly reduces the energy consumption in production, which is conducive to the large-scale industrial production of CNC. The nano-micro jet homogenization auxiliary means used in the present invention has high efficiency, short aging, simple feeding and discharging methods, and can be homogenized to separate CNC from the fiber, and evenly reduce the size of the fiber slurry, thereby greatly improving the yield of CNC and residual CNF. The maleic acid used in the present invention can be successfully recovered and recycled, and the recovery rate is more than 85%, and the CNC yield after reuse is less reduced. The obtained CNC has good dispersion stability and good thermal stability, and the above excellent performance increases its application potential in various types of reinforcing materials.

Claims

1. A method for preparing cellulose nanocrystals with controllable specifications by hydrolyzing cellulose with maleic acid using ferric chloride as catalyst and microfluidics as mechanical aid, characterized in that: The following steps are involved: S1. Prepare an aqueous maleic acid solution, a ferric chloride solution, mix and heat in a container, and add a cellulose raw material to perform a hydrolysis reaction; S2. The hydrolyzed fiber suspension is vacuum filtered and washed to obtain a filtrate and a filter residue, and a mixture of maleic acid and ferric chloride is recovered from the filtrate; S3. The filter residue in S2 is dialyzed with deionized water to obtain the retained solution; S4. The retained solution after dialysis is diluted with deionized water and homogenized by a nano-microfluidizer to obtain a colloidal nanocellulose mixture; S5. Centrifuge the nanocellulose mixture to obtain a light blue and transparent supernatant of cellulose nanocrystals dispersed in water. Collect the turbid liquid to obtain a cellulose nanofibril suspension. After drying, solid cellulose nanocrystals or cellulose nanofibrils can be obtained.

2. The method for preparing cellulose nanocrystals with controllable specifications by ferric chloride catalysis and microfluidic mechanical assistance of maleic acid hydrolysis according to claim 1, characterized in that: In step S1, the cellulose raw material is one or more of microcrystalline cellulose, bleached bagasse pulp, bleached wood pulp, bleached straw pulp, bleached cotton pulp, and bleached bamboo pulp.

3. The method for preparing cellulose nanocrystals with controllable specifications by ferric chloride catalysis and microfluidic mechanical assistance of maleic acid hydrolysis according to claim 1, characterized in that: In step S1, the mass concentration of maleic acid in aqueous solution is 50%-80%, the mass ratio of cellulose raw material to maleic acid aqueous solution is 1:20, and the reaction temperature is 80-100°C.

4. The method for preparing cellulose nanocrystals with controllable specifications by ferric chloride catalysis and microfluidic mechanical assistance of maleic acid hydrolysis according to claim 1, characterized in that: In step S1, the mass ratio of ferric chloride to maleic acid in the ferric chloride solution is 0.259-2.

333.

5. The method for preparing cellulose nanocrystals with controllable specifications by ferric chloride catalysis and microfluidic mechanical assistance of maleic acid hydrolysis according to claim 1, characterized in that: In step S1, the speed of mechanical stirring used when adding cellulose raw material is 300-500 r / min, and the time of the hydrolysis reaction is 0.5-6 hours.

6. The method for preparing cellulose nanocrystals with controllable specifications by ferric chloride catalysis and microfluidics mechanical assistance of maleic acid hydrolysis according to claim 1, characterized in that: In step S2, the vacuum filtration is carried out using a G4 sand core funnel, and deionized water is continuously added for filtration and washing, and the mass ratio of deionized water to maleic acid aqueous solution is 6-8; the method for recovering maleic acid in the filtrate includes rotary evaporation, cooling crystallization and reduced pressure distillation.

7. The method for preparing cellulose nanocrystals with controllable specifications by hydrolyzing cellulose with maleic acid catalyzed by ferric chloride and assisted by microfluidics according to claim 1, characterized in that: In step S3, the dialysis treatment is to dialyze the filter residue with deionized water until the conductivity is the same as that of the deionized water; the retained liquid is the material in the dialysis bag that has not been dialyzed out of the bag.

8. The method for preparing cellulose nanocrystals with controllable specifications by hydrolyzing cellulose with maleic acid catalyzed by ferric chloride and assisted by microfluidics according to claim 1, characterized in that: In step S4, the microfluidizer uses a high-pressure reaction chamber, the homogenization pressure is 9000 psi-16000 psi, and the homogenization times are 3 to 7 times.

9. The method for preparing cellulose nanocrystals with controllable specifications by hydrolyzing cellulose with maleic acid catalyzed by ferric chloride and assisted by microfluidics according to claim 1, characterized in that: In step S5, the centrifugal condition is 8000-10000 r / min, and the supernatant is collected by centrifugation for 15-20 min, which is light blue cellulose nanocrystals; in step S5, the drying is freeze-drying or spray-drying.

10. A white cellulose nanocrystal prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing cellulose nanocrystals by combining mechanical-assisted organic acid hydrolysis with ultrasound

    CN111116763A

  • Method for preparing cellulose nanofibrils (CNF) through metal salt / organic acid synergistic treatment

    CN113105563A

  • Method for cleanly preparing cellulose nanocrystal through one-step method combining organic acid hydrolysis with nanometer microjet homogenization and product

    CN113718543A